Analysis of Marketing Aspects of Innovative Entrepreneurship in the Regions - TALIMOVA, Lazat; AKHMETOVA, Zauresh; NAKIPOVA, Gulmira; BESPAYEVA, Roza; KUTTYBAEVA, Nurgul (Journal of Advanced Research in Law and Economics, 2018)
The article describes the marketing aspects of the innovation policy of the region. It has proved that modern marketing tools are able to determine the economic interest of economic entities in the development and implementation of innovations. The role of marketing tools in solving such important tasks of innovative entrepreneurship in the regions of Kazakhstan as increasing competitiveness and recognition of their products, increasing attractiveness for potential investors. It has proved that the state of regional marketing of innovations has a decisive influence on the methods of organization and intensity innovation processes in the economy, the level of development of innovative entrepreneurship at the regional level. The possibilities of marketing to attract innovative investors and promote innovative products are considered. The dynamics of innovative entrepreneurship in the regions of Kazakhstan has shown. The tools of state support of innovations are considered, some problems of marketing aspects of innovative entrepreneurship had revealed, and ways of their decision had offered.